The Impact of Private Label Brands on Managing the Supply Chain - Drachuk, Vera (2010)
Private label brands, or store brands, became an ubiquitous part of retailer offerings, especially in developed markets. Retail chains launch PL programs in order to increase customer loyalty, gain higher margins and rise their power over brand manufacturers. Private label brands are introduced across various product categories, from food to electronics, by positioning them in different price segments (from value to premium). The presence of these additional items in retail store makes the whole supply chain more complex with new risks and challenges involved, hence each category should be managed in the specific way in terms of designing new supply network. The research reveals factors that have an impact on this process: 1) type of product (innovative or functional) and PL type (value, “me-too” or premium); 2) level of existing bargaining power of the retailer in the market; and 3) the international factor which implies particular market specificity (case of Russia as an emerging market, as compared to UK industry).